2018
DOI: 10.1108/ijccsm-03-2017-0054
|View full text |Cite
|
Sign up to set email alerts
|

Migrants’ remittances

Abstract: Purpose The much-trumpeted Green Climate Fund and several other official financial mechanisms for financing adaptation to climate change under the UN Framework Convention on Climate Change have fallen short in meeting adaptation needs. Many poorer people are still grappling with the scourge of climate change impacts. Consequently, there has been a dominant research focus on climate change financing emanating from official development assistance (ODA), Adaptation Fund, public expenditure and private sector supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 36 publications
(62 reference statements)
0
23
0
Order By: Relevance
“…Indeed, when enabled to escape conditions of economic/environmental hardship and provided with equitable access to quality healthcare services along migration routes and in destination countries, individuals can prevent diseases and maintain good health along the migration process ( Schwerdtle et al., 2018 ). Additionally, through sending remittances back home, climate migrants can support local adaptation and resiliency-building within their communities, improving both social and environmental determinants of health in otherwise climate-vulnerable settings ( International Organization for Migration 2023 ; Musah-Surugu et al., 2018 ; Hassan and Mahmud, 2021 ). With regards to the broader health status of migrant receiving communities, recently developed dynamic simulation models have shown that policies which restrict access to healthcare and environmental health services for climate migrants may harm the net health of all residents ( Reuveny, 2021 ).…”
Section: Migration As Adaptation and The Global Charter For The Publi...mentioning
confidence: 99%
“…Indeed, when enabled to escape conditions of economic/environmental hardship and provided with equitable access to quality healthcare services along migration routes and in destination countries, individuals can prevent diseases and maintain good health along the migration process ( Schwerdtle et al., 2018 ). Additionally, through sending remittances back home, climate migrants can support local adaptation and resiliency-building within their communities, improving both social and environmental determinants of health in otherwise climate-vulnerable settings ( International Organization for Migration 2023 ; Musah-Surugu et al., 2018 ; Hassan and Mahmud, 2021 ). With regards to the broader health status of migrant receiving communities, recently developed dynamic simulation models have shown that policies which restrict access to healthcare and environmental health services for climate migrants may harm the net health of all residents ( Reuveny, 2021 ).…”
Section: Migration As Adaptation and The Global Charter For The Publi...mentioning
confidence: 99%
“…e Examples of policy measures that support migrants' investments include the 3×1 Program for Migrants in Mexico, through which national authorities provide three dollars for every one dollar of remittances invested in community projects; or loans offered by the Senegalese Government to diasporas. f a IOM, 2017c:81;Musah-Surugu et al, 2018. b Samuwai and Maxwell Hills, 2018.…”
Section: Maximizing Migrants' Contributions To Climate Actionmentioning
confidence: 99%
“…Thus, migration impacts rural areas' socioeconomic sustainability when its influences are not only current but ongoing. Through urbanto-rural flows (e.g., remittances, return migration), migrants contribute to present rural development through remittance investment (e.g., improving household welfare, educating children, donating to improve infrastructure, [16][17][18][19][20]). Additionally, returning migrants' knowledge and skills accumulated during the migration period can be utilized (e.g., to transform rural areas by improving the contractural relationship between rural areas and businesses and thus creating solid social capital, [21]) to contribute to the home community's development.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, returning migrants' knowledge and skills accumulated during the migration period can be utilized (e.g., to transform rural areas by improving the contractural relationship between rural areas and businesses and thus creating solid social capital, [21]) to contribute to the home community's development. When migrants' behavior reflects their notice of both society's and the future generation's benefit, their current investments and behaviors can influence future rural development [2,[19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation